2021
DOI: 10.1371/journal.pbio.3001060
|View full text |Cite
|
Sign up to set email alerts
|

Ectoderm to mesoderm transition by down-regulation of actomyosin contractility

Abstract: Collective migration of cohesive tissues is a fundamental process in morphogenesis and is particularly well illustrated during gastrulation by the rapid and massive internalization of the mesoderm, which contrasts with the much more modest movements of the ectoderm. In the Xenopus embryo, the differences in morphogenetic capabilities of ectoderm and mesoderm can be connected to the intrinsic motility of individual cells, very low for ectoderm, high for mesoderm. Surprisingly, we find that these seemingly deep … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 38 publications
2
25
1
Order By: Relevance
“…Our results indicate that the deep SE cells do not have a migratory capacity, in contrast with a previous study (Morita et al, 2012). These results agree both with the fact that deep ectoderm cells from gastrula embryos are not migratory (Kashkooli et al, 2021), and with the fact that SE explants developed up to tailbud stages never display any migratory behaviour. Using live imaging we show that the SE movement mirrors the movement of the NP, and its movement is directly influenced by NP morphogenesis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results indicate that the deep SE cells do not have a migratory capacity, in contrast with a previous study (Morita et al, 2012). These results agree both with the fact that deep ectoderm cells from gastrula embryos are not migratory (Kashkooli et al, 2021), and with the fact that SE explants developed up to tailbud stages never display any migratory behaviour. Using live imaging we show that the SE movement mirrors the movement of the NP, and its movement is directly influenced by NP morphogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…However, this is in contrast with studies showing that excised NP explants can elongate and roll up ( Vijayraghavan and Davidson, 2017 ). Furthermore, the argument supporting an active movement of deep epidermal cells is inconsistent with the fact that that deep ectoderm cells from gastrula-stage embryos, unlike mesodermal cells, do not have the capacity to migrate when explanted from the embryo ( Kashkooli et al, 2021 ). In order to examine whether deep SE cells become migratory during neurulation and differ from their gastrula-stage counterparts, we explanted deep SE cells from stage 14 allowed them to attach to fibronectin (FN)-coated substrates and subsequently generated time-lapse recordings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the ectoderm-to-mesoderm transition depends on the inhibition of ROCK signaling and the overexpression of Rnd1 and Shirin; these factors promote cell migration or mesodermal transition due to the downregulation of actomyosin contractility, which leads to the activation of the Hippo signaling pathway [ 118 ].…”
Section: Nanomechanical-based Differentiation and Specification Of Th...mentioning
confidence: 99%
“…François Fagotto (Montpellier Cell Biology Research Centre, Montpellier, France) explored how the Rho pathway controls cell stiffness during Xenopus gastrulation. He demonstrated that the downregulation of Rho kinases (Rock)-dependent actomyosin contractility triggers ectoderm-to-mesoderm transition (Kashkooli et al, 2021). Another paradigmatic example of drastic changes in cellular movements can be found during zebrafish development.…”
Section: Engineering Shape and Form In Synthetic Systemsmentioning
confidence: 99%